2013
DOI: 10.1108/jsbed-01-2012-0012
|View full text |Cite
|
Sign up to set email alerts
|

IT readiness in small firms

Abstract: Purpose – The aim of the paper is to explore conceptually and empirically the application of the concept of IT readiness to small firms. Design/methodology/approach – The approach taken was a questionnaire administered to small manufacturing business owners in the Liguria region of Italy. Data were analysed using factor and cluster analysis. Findings – IT readiness concept appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
4
32
0
3
Order By: Relevance
“…The dynamic capability framework fits well with our focus on intellectual alignment because it provides a framework to consider how resources, planning, and people all influence alignment (Weill, Subramani, & Broadbent, 2002). Orser et al (2000), Street & Cameron (2007) IT resources Matthews (2007), Spinelli et al (2013), Polo Peña et al (2011) Strategic planning and planning time horizons…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic capability framework fits well with our focus on intellectual alignment because it provides a framework to consider how resources, planning, and people all influence alignment (Weill, Subramani, & Broadbent, 2002). Orser et al (2000), Street & Cameron (2007) IT resources Matthews (2007), Spinelli et al (2013), Polo Peña et al (2011) Strategic planning and planning time horizons…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Research recognizes IT use as an SME growth factor, but cost often prevents SMEs from acquiring IT infrastructure (Matthews, 2007). IT readiness of the small business is an important precondition for implementing new systems (Spinelli, Dyerson, & Harindranath, 2013), and research has shown an IT infrastructure that enables other types of business strategies to have a positive effect on performance (Polo Peña, Frías Jamilena, & Rodriguez Molina, 2011). The type and amount of installed IT, or legacy systems, also have an influence on how small businesses adapt (Wynn, Turner, & Lau, 2013) where the ability to change direction or strengthen a capability can be limited by an SME's ability to integrate existing and new infrastructure (Woznica & Healy, 2009).…”
Section: Characteristics Of Small and Medium-sized Enterprises (Smes)mentioning
confidence: 99%
“…Spinelli et al . () attribute lower adoption rates and less sophisticated engagement to a lack of strategic deployment of ICT in small firms. It is therefore to strategy, ICT, and the small firm that we now turn.…”
Section: Ict Small Firms and Very Small Firmsmentioning
confidence: 99%
“…Advances in IT lead to increasing levels of technology adoption and use in SMEs and technology is pushed further and further into their processes and operations, as shown by management literature. As IT is now used by many competitors and suppliers in their operations, it is necessary that executives and researchers be aware of how the alignment of business and IT impacts firms [26][27][28]. For all the above stated reasons the purpose of this paper is to indicate all the phases of Strategic Information Systems Planning (SISP) process that contribute to a greater extent of IS planning success as well as to provide IT managers with recommendations in terms of their implementation.…”
Section: Introductionmentioning
confidence: 99%